Application of the Quadruple Helix Model and Feed Processing Technology in Supporting Good Breeding Practice at Bali Cattle Breeding in Parepare City - Zulkharnaim zulkharnaim; Syahdar Baba; Fadlirrahman Latief; Indrawirawan Indrawirawan; Aulia Uswa Noor; Aulisani Annisa (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
The beef cattle population in Bacukiki District experienced a low growth rate from 2015 to 2019. This was due to the absence of an empowerment program or model of cooperation that brought together relevant stakeholders and the lack of information regarding beef cattle farming technology. Farmers really need an increase in livestock and institutional capacity through technological innovation in overcoming problems and utilizing the potential of available regional resources. The Hasanuddin University Community Service Program-Partnership-Community Program (PPMU-PK-M) which was held at the Liae Livestock Farmers Group, Watang Bacukiki Village aims to increase the capacity of farmers through training. There were two solutions offered in this activity: 1) conducting Focus Group Discussions (FGD) in order to apply the Quadruple Helix concept and 2) providing technical training related to Good Breeding Practice in terms of feed management and processing. The results of the FGD were in the form of agreements and consolidation regarding the application of the Quadruple Helix model and the role of each stakeholder. Farmers carefully and enthusiastically participated in feed processing technology training in an effort to achieve Good Breeding Practice. The application of the Quadruple Helix model in Bali cattle breeding can support the achievement of Good Breeding Practice in Parepare City so that it can become a model for other areas in the vicinity.